DETERMINAN INFEKSI OPORTUNISTIK KRIPTOSPORIDIOSIS PADA ODHA (ORANG DENGAN HIV/AIDS) DI RS GUNTUR KABUPATEN GARUT - Diani, Yuli Ayu; Wahyono, Tri Yunis Miko (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Human Immunodeficiency Virus (HIV) is a virus that infects, destroys, and disrupts the human immune system, causing progressively low immunity. HIV infection is a still a major global health problem. Opportunistic infection (OI) are the main cause of morbidity and mortality in person living HIV/AIDS (PLHIV) because OI contributes 80% to the cause of death of PLHIV. Cryptosporidiosis is one of the OI that caused by the protozoa Cryptosporidium sp. which is an obligate intracellular parasite that causes diarrhea in human and animals. This study aims to identify the determinants associted with cryptosporidiosis OI at Guntur Hospital, Garut Regency. Methods: The case-control strudy design was carried out using pre-ART register data and medical records of PLHIV at Guntur Hospital, Garut Regency in November 2022. The total sample was 180 consisting of 40 cases and 140 controls. Univariate, bivariate analysis using chi-square, and multivariate analysis with logistic regression was performed. Result: Logistic regression test alaysis obtained a statistically significant relationship between HIV stage and cryptosporidiosis (OR=32,97; 95% CI: 7,40-146,90) with a p-value <0,001, but there was no significant relationship statistically between age, gender, education, employment status, marital status, risk of sexual behavior, history of injection drugs, and ART adherence. Conclusion: The determinants of crypstosporidiosis in PLHIV are advances clinical stages of HIV, stages III and IV. Suggestion: It is necessary to prevent OI so that the early stages do not progress to advanced stages through the intervention of various epidemiological, social, and human activity factors.